Assembly of hollow mesoporous nanoarchitectures composed of ultrafine Mo2C nanoparticles on N-doped carbon nanosheets for efficient electrocatalytic reduction of oxygen. Issue 6 (9th October 2017) - Guo, Yanna; Tang, Jing; Henzie, Joel; Jiang, Bo; Qian, Huayu; Wang, Zhongli; Tan, Haibo; Bando, Yoshio; Yamauchi, Yusuke
Abstract : A simple method is developed to prepare Mo2 C-embedded mesoporous N-doped carbon nanosheets which assemble into hollow spheres. Abstract : A simple method is developed to assemble Mo2 C nanocrystals on the surfaces of hollow, highly conductive mesoporous nanoparticles. Diblock copolymer (PS- b -PEO) micelles are used as templates to assist in the fast complexation of molybdate (MoO4 2− ) and polydopamine (PDA) precursors to make hollow precursor MoO4 2− /PDA/PS- b -PEO particles. Then these particles are carbonized to generate mesoporous N-doped carbon nanosheets riddled with ultrafine molybdenum carbide (Mo2 C) nanoparticles (MMo2 C/NCS). An N-doped carbon matrix serves as an electron conductor and helps to prevent the aggregation of the Mo2 C nanoparticles. The Mo2 C nanoparticles in turn enhance the catalytic performance for the oxygen reduction reaction (ORR). The unique mesoporous 2D nanosheet and its derived 3D hollow structure expose numerous active catalytic sites while enabling free diffusion of the electrolyte and mass transfer. Based on these properties, MMo2 C/NCS show enhanced catalytic activity for the ORR.